DEVELOPMENT E-PORTFOLIO AS A MODEL OF AUTHENTIC ASSESSMENT - Lamberthus J Lokollo; J L Kundre (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2021)
Authentic assessment is an essential component of effective learning that links theory to practice. As information technology has developed, portfolios have been considered authentic environments to enable learning students to reflect their potential through the evidence presented in the e-portfolio. This research's general objective is to produce an e-portfolio based authentic assessment model for the PNFI Learning Media Development course in the Non-formal Education Study Program, Faculty of Teacher Training and Education, Universitas Pattimura. The method used in this research is the development research method. It uses three main stages of the Tjeer Plomp model: 1) preliminary research, 2) prototype design and development and expert validation, and 3) testing and revision. This study involved 71 students of the Faculty of Teacher Training and Education, Universitas Pattimura, and three experts in assessment, media, and learning technology. The research data were obtained through interviews, questionnaires, and observations. This study found that Mahara is a suitable platform to be used in the learning process and is recommended to be developed as an e-portfolio based authentic learning model in the Non-formal Education Study Program, Faculty of Teacher Training and Education, Universitas Pattimura